3D geophysical modelling of the Bethlehem sub-basin, Free State, South Africa - Naidoo, Ansuya (My University, 2020)
Extensions to the Witwatersrand Basin have been widely examined, with many geophysical surveys being carried out in the early 1990s. One of these areas is the Bethlehem sub-basin, located on the south eastern edge of the Witwatersrand basin. The aim of the study is to integrate old geophysical datasets to create a 3D geological and a 3D gravity forward model of the Bethlehem Sub - basin. A re – interpretation of the Bethlehem sub-basin was done using the latest geophysical software and techniques. The study also investigates the cause of the Bethlehem gravity high. The outcome of this study provides a more constrained interpretation of the structure of the Bethlehem sub-basin and its relationship to the Witwatersrand Basin. The resultant 3D gravity model shows the Bethlehem Sub - basin is structurally controlled by north northwest trending horsts and grabens of granite and West Rand Group rocks respectively. These grabens preserve large-scale West Rand Group sediments of the Witwatersrand Supergroup. The horst and graben structures creates a change in density from low density granite to high density West Rand Group, causing the gravity high seen in the Bethlehem area. Four major structures were interpreted in the seismic and gravity data. These are labelled as fault B, C, D and E. Normal faults B and C trending north northwest create a granite ridge underlying the Karoo Supergroup. Normal faults D and E create a smaller granite ridge overlain by West Rand Group sediments. This study investigates the ability to integrate existing 2D datasets into a 3D space and the significance of viewing data in a 3D environment to better understand and constrain lithological structures and boundaries
A dissertation submitted to the Faculty of Science, in fulfilment of the requirements for the degree of Master of Science, University of the Witwatersrand, Johannesburg, 2020